Enhanced anti-infective activities of sinapic acid through nebulization of lyophilized protransferosomes - Alhadrami, Hani A.; Gamal, Amr; Amaeze, Ngozi; Sayed, Ahmed M.; Rateb, Mostafa E.; Naguib, Demiana M. (Frontiers in Nanotechnology, 2025)
IndroductionCOVID-19 is a contagious illness caused by the virus SARS-CoV-2, a major cause of death globally, even with effective vaccinations. Additionally, multidrug resistant bacterial and fungal pathogens are a real threat to many healthcare settings. Sinapic acid (SA), isolated from different plants or marine algae, has been reported to have antioxidant, antibacterial, and antiviral properties. Although there is evidence that SA has anti-SARS-CoV-2 activity, it is poorly absorbed when taken orally due to its intestinal metabolism. The current study aimed to improve SA's activity against SARS-CoV-2, different bacterial and fungal pathogens, bioavailability, and targeting using a nebulized, freeze-dried, transferosomal formulation.MethodsA response-surface experimental study using phospholipid, cholesterol, and surfactants was employed to develop transferosomes. Various formulations were prepared and characterized for entrapment efficiency (EE), release, and size to select the optimized formulation. It was then lyophilized into a powder to be evaluated in vivo for its pharmacokinetic properties.Results and discussionSA exhibited antibacterial and antifungal activity, with SA-protransferosomes showing enhanced effectiveness compared to that of pure SA and approaching the efficacy of positive controls. Notably, SA protransferosomes demonstrated activity comparable to that of ciprofloxacin against E. faecalis and S. mutans and were effective against Candida albicans and Aspergillus niger, similar to nystatin. The optimized formula significantly enhanced the SARS-CoV-2 activity (IC50 = 0.016 ± 0.008 μg/mL), Cmax by 2.27 times, and AUC (0–∞) by 5.4 times, as compared to pure SA. As a result, the use of nebulized SA-transferosomes can be regarded as a safe and efficient strategy to counter different infections.